On Some Inequalities Concerning Rate of Growth of Polynomials (Analysis in Theory and Applications, 2014)
In this paper we consider a class of polynomials $P(z)= a_{0} + \sum_{v=t}^{n} a_{v}z^{v}$, $t≥ 1,$ not vanishing in $|z|
Keywords: Polynomial; zero; inequality.